Chagas disease: what is known and what is needed - A background article - José Rodrigues Coura (Memorias do Instituto Oswaldo Cruz, 2007)
Chagas disease began millions of years ago as an enzootic disease of wild animals and started to be transmitted to man accidentally in the form of an anthropozoonosis when man invaded wild ecotopes. Endemic Chagas disease became established as a zoonosis over the last 200-300 years through forest clearance for agriculture and livestock rearing and adaptation of triatomines to domestic environments and to man and domestic animals as a food source. It is estimated that 15 to 16 million people are infected with Trypanosoma cruzi in Latin America and 75 to 90 million people are exposed to infection. When T. cruzi is transmitted to man through the feces of triatomines, at bite sites or in mucosa, through blood transfusion or orally through contaminated food, it invades the bloodstream and lymphatic system and becomes established in the muscle and cardiac tissue, the digestive system and phagocytic cells. This causes inflammatory lesions and immune responses, particularly mediated by CD4+, CD8+, interleukin-2 (IL) and IL-4, with cell and neuron destruction and fibrosis, and leads to blockage of the cardiac conduction system, arrhythmia, cardiac insufficiency, aperistalsis, and dilatation of hollow viscera, particularly the esophagus and colon. T. cruzi may also be transmitted from mother to child across the placenta and through the birth canal, thus causing abortion, prematurity, and organic lesions in the fetus. In immunosuppressed individuals, T. cruzi infection may become reactivated such that it spreads as a severe disease causing diffuse myocarditis and lesions of the central nervous system. Chagas disease is characterized by an acute phase with or without symptoms, and with entry point signs (inoculation chagoma or Romaña's sign), fever, adenomegaly, hepatosplenomegaly, and evident parasitemia, and an indeterminate chronic phase (asymptomatic, with normal results from electrocardiogram and x-ray of the heart, esophagus, and colon) or with a cardiac, digestive or cardiac-digestive form. There is great regional variation in the morbidity due to Chagas disease, and severe cardiac or digestive forms may occur in 10 to 50% of the cases, or the indeterminate form in the other asymptomatic cases, but with positive serology. Several acute cases have been reported from Amazon region most of them by T. cruzi I, Z3, and a hybrid ZI/Z3. We conclude this article presenting the ten top Chagas disease needs for the near future.